Treatment of superficial vein thrombosis with intermediate dose of tinzaparin: A real word cohort study – The SeVEN EXTension study. (July 2021) - Karathanos, Christos; Chatzis, Dimitrios; Latzios, Panagiotis; Papakostas, Ioannis; Goumas, Konstantinos; Giannoukas, Athanasios D; ,
Background: To assess the treatment of superficial vein thrombosis (SVT) with intermediate dose of tinzaparin in a setting of real world practice. Methods: Prospective observational study of consecutive patients treated by vascular physicians in the private sector with tinzaparin (131 IU/Kg) once daily. Treatment duration was at the treating physician's discretion. The outcomes of the study were symptomatic venous thromboembolism, extension of thrombus and bleeding complications. Results: 660 patients were included and followed up for at least 3 months. Median duration of treatment was 30 days (14–120). History of prior deep vein thrombosis (HR 2.77; 95% CI= 1.18–6.49; p = 0.018) and current SVT above the knee (HR1.84; 95% CI = 1.33–3.53; p = 0.0002) were associated with prolonged treatment duration. Primary efficacy outcomes occurred in 20 (3%) patients. The median time to the event was 24 (6–92) days and was not related to treatment duration. Conclusions: Tinzaparin at intermediate dose is an effective and safe treatment for SVT.